Men's Roles in Unpaid Domestic Work: A Case Study of Paternal Involvement in Indonesia - Evi Putrianti (Pusat Studi Gender Universitas Jember, 2026)
The contrasting realities of societies adhering to patriarchal cultural principles, alongside feminist discourse, constitute a compelling backdrop for the emergence of contemporary gender issues. In Indonesia, men frequently enjoy privileged rights, while women tend to occupy subordinate positions. Female subordination manifests across multiple domains, including the workplace, education, healthcare, and unpaid domestic labor within the household. The persistent failure to achieve gender equality in Indonesia is further exacerbated by marriage laws and labor division regulations that are widely regarded as inequitable. This condition stands in clear contradiction to the nation's foundational philosophy, religious values, and social movements that champion equality and justice for both women and men. The expanding patriarchal discourse particularly within the lives of housewives and working mothers serves as the primary object of inquiry into patterns of paternal involvement in Indonesian families. Employing a feminist literacy study approach, this research examines the documented trajectory of paternal involvement in Indonesia through digital spaces. This systematic literature review aims to analyze the double burden experienced by women, the relational dynamics concerning men's roles in unpaid domestic work, and the correlation between legal developments and gender issues in Indonesia. The findings reveal that fathers' roles in Indonesia remain minimal, with the double burden of childcare continuing to fall disproportionately on women. Married men in Indonesia are still predominantly defined by their instrumental role as breadwinners, while the active participation of men as husbands and fathers remain comparatively limited. This study affirms the urgent need for intervention programs that promote male engagement in domestic work and childcare in Indonesia.